Identifying potential change leaders through social network visualizations - Andrzejak, Piotr (Identyfikacja potencjalnych liderów zmiany z wykorzystaniem wizualizacji sieci społecznych, 2019)
Every organizational change is considered a big challenge. Even having assured enough of the resources needed to drive the change successfully, there is also the necessity to choose the people who would be able to properly lead the change. Organizational network analysis provides some techniques and methods that help in visualizing the informal organizational structure. In the following paper some of these will be presented with the emphasis on showing the potentially key persons for the change that is planned to be developed. In the presented case study one large company was examined. The aim of the article is to analyse the problem of choosing the right people to drive change. In order to select potential change leaders there is an algorithm proposed which takes into consideration two aspects. Namely, the intensity of the archetypical leadership value of the actor, and the actor’s position in the informal network. The results confirm that a relatively small group of change leaders can directly reach the majority of employees, which is one of the crucial factors for the change to succeed. The visualizations used in the study can shorten the time needed to find the right people to drive the change, and also reduce the probability of wrong guesses provided by the intuition.
Management Sciences = Nauki o Zarządzaniu, 2019, vol. 24, no. 1; s. 37-47
Keywords: organizational change; organizational network analysis; network visualizations; zmiana w organizacji; analiza sieci organizacyjnych; wizualizacje sieci